The Value of Intraoperative Parathyroid Hormone Monitoring in Localized Primary Hyperparathyroidism: A Cost Analysis - Morris, Lilah F. (Springer-Verlag, 2009)
BACKGROUND: Minimally invasive parathyroidectomy (MIP) is the preferred approach to primary hyperparathyroidism (PHPT) when a single adenoma can be localized preoperatively. The added value of intraoperative parathyroid hormone (IOPTH) monitoring remains debated because its ability to prevent failed parathyroidectomy due to unrecognized multiple gland disease (MGD) must be balanced against assay-related costs. We used a decision tree and cost analysis model to examine IOPTH monitoring in localized PHPT. METHODS: Literature review identified 17 studies involving 4,280 unique patients, permitting estimation of base case costs and probabilities. Sensitivity analyses were performed to evaluate the uncertainty of the assumptions associated with IOPTH monitoring and surgical outcomes. IOPTH cost, MGD rate, and reoperation cost were varied to evaluate potential cost savings from IOPTH. RESULTS: The base case assumption was that in well-localized PHPT, IOPTH monitoring would increase the success rate of MIP from 96.3 to 98.8%. The cost of IOPTH varied with operating room time used. IOPTH reduced overall treatment costs only when total assay-related costs fell below $110 per case. Inaccurate localization and high reoperation cost both independently increased the value of IOPTH monitoring. The IOPTH strategy was cost saving when the rate of unrecognized MGD exceeded 6% or if the cost of reoperation exceeded $12,000 (compared with initial MIP cost of $3733). Setting the positive predictive value of IOPTH at 100% and reducing the false-negative rate to 0% did not substantially alter these findings. CONCLUSIONS: Institution-specific factors influence the value of IOPTH. In this model, IOPTH increased the cure rate marginally while incurring approximately 4% additional cost.